Manajemen Budaya dan Motivasi Kerja Kepala Madrasah Terhadap Profesionalisme Guru dalam Meningkatkan Mutu Pendidikan di Madrasah Aliyah Al-Ishlah Sukadamai Lampung Selatan - Siti Maesaroh; Taqwatul Uliyah; Endang Ekowati (Journal on Education, 2024)
This exploration plans to portray the Social Administration and Work Inspiration of Madrasah Heads on Educator Impressive skill in Working on the Nature of Schooling at Madrasah Aliyah Al-Ishlah Sukadam Natar, South Lampung. This sort of examination is subjective. Scientists assume an immediate part as information gatherers coming about because of top to bottom perceptions and are effectively engaged with research. Information is taken from witnesses or respondents during interviews, while extra information is as reports. Aside from interviews, the information got was additionally acquired from perception and documentation. Information investigation is done by exploring existing information. Then do information decrease, information show, end drawing and the last phase of information examination. The examination results show that: The work culture of the madrasa head at Mama Al Islah Sukadam is great so it can increment educator impressive skill and, surprisingly, the nature of schooling will likewise increment. The current work culture incorporates the propensity for leaving early and the way of life of shaking hands. The current work program gives the educator board the chance to participate in a few preparation phases and studios on Instructor Impressive skill. Execution of Oversight of Madrasah Heads. The work inspiration of the Head of Madrasah Mama Al Islah Sukadam is great so it can increment instructor incredible skill and, surprisingly, the nature of training will likewise increment. The current inspiration incorporates giving prizes to instructors who are model and giving discipline to educators who are bad. The work culture and work inspiration at Mama Al Islah Sukadam are great so it can increment instructor amazing skill and, surprisingly, the nature of schooling will likewise increment.